VD_FINDINFO HC / 2016 / 246 vom 2. März 2016 - VD Tribunal cantonal (2016)
SUCCESSION, BÉNÉFICE D'INVENTAIRE, VOIE DE DROIT PRÉMATURÉE, DÉCISION D'IRRECEVABILITÉ | 553 CC, 580 CC, 322 al. 1 CPC (CH), 117 CDPJ, 118 CDPJ